Distance to a Plastic Surgeon and Type of Insurance Plan Are Independently Predictive of Postmastectomy Breast Reconstruction. Issue 2 (August 2016) - Roughton, Michelle C.; DiEgidio, Paul; Zhou, Lei; Stitzenberg, Karyn; Meyer, Anne Marie
Abstract : Background: The psychosocial benefits of postmastectomy breast reconstruction are well established; however, health care barriers persist. The authors evaluated statewide patient population to further identify obstacles to reconstruction. Methods: A linked data set combining the North Carolina Central Cancer Registry with administrative claims from Medicare, Medicaid, and private insurance plans identified women diagnosed with breast cancer from 2003 to 2006. For inclusion in the study, women must have had a mastectomy within 6 months of diagnosis and had continuous insurance enrollment at least 2 years postoperatively ( n = 5381). Multivariable logistic regression was used to model odds of reconstruction. Results: Approximately 20 percent underwent reconstruction ( n = 1130). Distance to a plastic surgeon—10 to 20 miles (OR, 0.78) and greater than 20 miles (OR, 0.73; p < 0.05)—was significantly predictive of no reconstruction, independent of other well-known disparities, including age, race, rural location, and lower household income. Women with government-funded health care, such as Medicare (OR, 0.58) and Medicaid (OR, 0.24; p < 0.001), were also significantly less likely to undergo reconstruction. Consistent with previous study, advanced cancer stage and receipt of radiation therapy decreased the likelihood of reconstruction. Furthermore, when the authors compared immediate to delayed reconstruction, rural location, chemotherapy, and radiation therapy were significantly predictive of delay. Conclusions: This is the first population-based study to demonstrate distance to care and insurance plan as significant predictors of receipt of reconstruction. Additional research is needed to understand health care barriers and to determine whether distance to a plastic surgeon can be ameliorated by outreach programs. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III. Abstract : This and Related "Classic" Articles Appear on Prsjournal.Com for Journal Club Discussions.